The Open Book of Social Innovation - Murray, Robin; Caulier-Grice, Julie; Mulgan, Geoff (Young Foundation, NESTA, 2010)
This book is about the many ways in which people are creating new and more effective answers to the biggest challenges of our times: how to cut our carbon footprint; how to keep people healthy; how to end poverty. It describes the methods and tools for innovation being used across the world and across the different sectors – the public and private sectors, civil society and the household – and in the overlapping fields of the social economy, social entrepreneurship and social enterprise. It draws on inputs from hundreds of organisations around the world to document the many methods currently being used. In other fields, methods for innovation are well-understood. In medicine, science, and business, there are widely accepted ideas, tools and approaches. But despite the richness and vitality of social innovation, there is little comparable in the social field. Most people trying to innovate are aware of only a fraction of the methods they could be using. This book provides a first mapping of these methods and of the conditions that will enable social innovation to flourish.
Keywords: Libre accès; UK